Pengembangan Sistem Informasi Geografis Penanganan Bencana berbasis Website di Kota Malang - Galih Alhakim; Fatwa Ramdani; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Throughout 2019, until the end of October, BPBD of Malang City had recorded more than 184 disaster events, where the most frequent disasters were fires, landslides, fallen trees, puddles, earthquakes, and strong winds. The BPBD of the city of Malang also reported that during January - October the total damage and losses from the disaster were not less than Rp.10,695 billion. Lack of awareness of citizens about pre-disaster management and late reporting of disasters when disasters occur cause damage and losses that are caused to be very large. Based on these problems, the application of disaster management and reporting is needed so that people can report disaster events early so that they can reduce the risk of loss of life and property damage. The developed application must be easy to access and have an interface that makes it easy for the general public when accessing it. In developing this application, the writer uses the Waterfall methodology, the purpose is to use this methodology to work on applications that will be made based on the stages that have been previously designed. To make it easier to accommodate the modeling needs, the design of this application will be made in an object oriented manner and using an online map library to facilitate mapping of disaster data. In the process of implementation, the authors develop a website using the Codeigniter framework and a javascript-based online map library that is leafletjs and also google maps. Furthermore, the authors will test the application using White-Box Base-Path-Testing, and Black-Box Testing to determine the level of success of the implementation as well as testing the accuracy to find out how much the accuracy of a location from online maps compared with standard commercial GPS equipment. Based on the results of the study, it is known that the development of a geographic information system application based on website disaster management can accommodate existing engineering needs. And the results of the accuracy of GPS maps online with commercial GPS produces an average error margin of 39.7860457. The results of the design and implementation that have been carried out are proven to have an effect on making it easier for the community to submit disaster reporting.